Annual Research Review: Emergence of problem gambling from childhood to emerging adulthood: a systematic review. (8th November 2022) - Richard, Jérémie; King, Serena M.
Abstract : Background: The risk for problematic gambling and associated high‐risk behaviors is elevated during adolescence and emerging adulthood. Activities with gambling‐like features and novel forms of gambling may place youth at an increased risk for problem gambling. Aim and method: The aim of this review is to provide an overview of the association between both activities with gambling‐like features and novel gambling activities and problem gambling among youth while examining the role of psychopathology and cognitive processes. Six databases (PsychINFO, MEDLINE, PubMed, Social Work Abstracts, Technology Collection, and Scopus) were searched in November 2021 for peer‐reviewed articles investigating the association between the aforementioned variables among youth up to the age of 25 years. Risk of bias was assessed using the Observational Study Quality Evaluation. Findings: Forty‐five articles were included in the review. Positive associations were observed between engagement in activities with gambling‐like features (e.g., video games, social casino games, loot boxes) and problem gambling. Increased involvement with novel forms of gambling (e.g., online sports betting, fantasy sports, and esports betting) were also associated with a greater risk for problematic gambling. Males reported higher rates of engagement in these activities and a greater risk of problem gambling than females. Impulsivity, risk taking, cognitive distortions, and specific emotional vulnerabilities were associated with an increased risk of problem gambling. Conclusions: Despite the need for additional longitudinal research controlling for relevant confounders, these findings underline how engagement in activities with gambling‐like features are relevant in the developmental trajectory toward problem gambling.